2014
DOI: 10.1186/1129-2377-15-44
|View full text |Cite
|
Sign up to set email alerts
|

Elevated audiovisual temporal interaction in patients with migraine without aura

Abstract: BackgroundPhotophobia and phonophobia are the most prominent symptoms in patients with migraine without aura. Hypersensitivity to visual stimuli can lead to greater hypersensitivity to auditory stimuli, which suggests that the interaction between visual and auditory stimuli may play an important role in the pathogenesis of migraine. However, audiovisual temporal interactions in migraine have not been well studied. Therefore, our aim was to examine auditory and visual interactions in migraine.MethodsIn this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…Yang et al, (2014) studied visual-audio integration in migraine by varying the inter-stimulus interval of visual and auditory stimuli to investigate the length of the integration window. There was evidence of greater integration window in migraine compared to control groups when the visual stimulus was presented before the auditory signal consistent with the idea that these populations are hyperexcitable (Yang et al, 2014). Audiovisual stimuli lead to suppression effects: longer intervals (200 -300ms) between audio and visual stimuli tend to result in suppression of the second stimulus, as the two are no longer thought to be linked (Meredith et al, 1987).…”
Section: Visual-auditory Integrationsupporting
confidence: 66%
See 3 more Smart Citations
“…Yang et al, (2014) studied visual-audio integration in migraine by varying the inter-stimulus interval of visual and auditory stimuli to investigate the length of the integration window. There was evidence of greater integration window in migraine compared to control groups when the visual stimulus was presented before the auditory signal consistent with the idea that these populations are hyperexcitable (Yang et al, 2014). Audiovisual stimuli lead to suppression effects: longer intervals (200 -300ms) between audio and visual stimuli tend to result in suppression of the second stimulus, as the two are no longer thought to be linked (Meredith et al, 1987).…”
Section: Visual-auditory Integrationsupporting
confidence: 66%
“…Audiovisual stimuli lead to suppression effects: longer intervals (200 -300ms) between audio and visual stimuli tend to result in suppression of the second stimulus, as the two are no longer thought to be linked (Meredith et al, 1987). Yang et al, (2014) demonstrated less suppression from audio stimuli on visual stimuli in migraine compared to control groups when there was this longer inter-stimulus interval, also consistent with the idea of hyperexcitation in migraine.…”
Section: Visual-auditory Integrationsupporting
confidence: 58%
See 2 more Smart Citations
“…Recent studies, including those utilizing functional MRI, also provide evidence that other sensory input, such as light, sound and odor, are biologically amplified in patients with COPCs. [276][277][278][279][280][281] In these studies, the insula -the brain region that plays a critical role in sensory integration -most consistently shows hyperactivity. 282 283 Using experimental pain testing, two pathogenic mechanisms have been found to contribute to enhanced pain perception and low sensory thresholds in individuals with COPCs:…”
Section: Abnormal Pain and Sensory Processingmentioning
confidence: 92%